Effect of auricular acupoint pressing combined with acupoint application in the treatment of senile constipation (耳穴压豆联合穴位贴敷治疗老年性便秘效果观察) - KAN Haiying (坎海英); ZHOU Weihua (周维华) (中西医结合护理)
Objective To investigate the effect of auricular acupoint pressing combined with acupoint application in the treatment of senile constipation. Methods Totally 80 elderly patients with constipation were selected through simple random sampling based on drawing, and were placed in the control group and observation group, with 40 cases in each group. All patients received routine treatment and nursing, and those in the observation group received auricular acupoint pressing therapy combined with acupoint application. The constipation-related indicators and effect of nursing interventions were measured and compared between two groups. Results Shorter inter-defecatory time interval and defecation duration, and higher scores of defecation sensation and fecal Characteristics were observed in the observation group compared with those in the control group (P＜0. 05). The overall effective rate of nursing interventions in the observation group was higher than that in the control group (90. 00% vs. 72. 50%, P＜0. 01). Conclusion The auricular acupoint pressing combined with acupoint application is effective to relieve the constipation symptoms, showing a positive effect on recovery of elderly patients. (目的 分析耳穴压豆联合穴位贴敷治疗老年性便秘的效果。方法 选取2023年11月—2024年7月医院收治的老年性便秘患者为研究对象, 通过抽签法分为对照组和观察组, 各40例。对照组接受常规治疗和护理, 观察组在对照组基础上增加耳穴压豆结合穴位贴敷。评估患者排便相关指标, 对比两组护理干预效果。结果 观察组排便间隔时间和排便用时均较对照组缩短, 排便感觉和粪便性状评分优于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率90. 00%(36/40), 高于对照组的72. 50%(29/40), 差异有统计学意义(P＜0. 01)。结论 耳穴压豆联合穴位敷贴可以进一步改善老年患者的便秘症状, 对促进康复具有积极意义。)